Manoel de Barros: Intercessory poetry of smaller geographies in video - Belleza, Eduardo Oliveira (Geografares, 2014)
The notion of creating, by understanding the philosophy of Deleuze and Guattari - as something that acts with / about the world of mode promote someone difference - pushes us to move a specific concept that has been addressing about contemporary spatial thinking. Our exercise here is to think along with the concept of smaller geographies and some images produced by young residents of a neighborhood, located on the outskirts of the city of Campinas - SP, in a workshop of production of videos, in which we used the poetics of Manoel de Barros for to invent other ways to spell the living space of the participants. We believe that this concept helps us to face some problems and propose other ways / thoughts into the language of video, especially by shifting the image as a representation of the space and as likely to be represented.Keywords: Manoel de Barros; smaller geograhies; video.